Retraction notice to “Principles and concepts in designing Tropical-Shore settlement in Estuary ecosystem case study: Weriagar District, Bintuni Bay“ [Journal of Architecture and Urbanism, 42(2), 169–176] - Firmansyah, Firmansyah; Wulanningsih, Resya; Nidia Kusuma, Bintang; Rante Allo, Ira Prayuni (Journal of Architecture and Urbanism, 2023)
The following article is being retracted from publication in Journal of Architecture and Urbanism:Principles and concepts in designing Tropical-Shore settlement in Estuary ecosystem case study: Weriagar District, Bintuni Bay, by Firmansyah Firmansyah, Resya Wulanningsih, Bintang Nidia Kusuma, Ira Prayuni Rante Allo, Volume 42, Issue 2, pp. 169–176, Journal of Architecture and Urbanism, 2018https://doi.org/10.3846/jau.2018.6486https://journals.vilniustech.lt/index.php/JAU/article/view/6486Since the same results were published in IOPP articlePrinciples and concepts in designing tropical-shore settlement in estuary ecosystem, case study: Weriagar District, Bintuni Bay, by Firmansyah, Bintang Nidia Kusuma, Ira Prayuni and Aldo Fernando, Volume 99, Article ID 012036, IOP Conference Series: Earth and Environmental Science, International Conference on Sustainability in Architectural Design and Urbanism 2017 9–10 August 2017, Semarang, Indonesiahttps://doi.org/10.1088/1755-1315/99/1/012036Submitted: 4 November 2017; CTA: 16 December 2017; Accepted: 5 December 2017; Published: 5 January 2018 under licence by IOP Publishing Ltd.The Editors and publishers of the journal, Vilnius Gediminas Technical University, note that we received, peer-reviewed, accepted and published the article on the basis that the authors are presenting original results and are not intending to publish them in any other journal.The retracted article will remain online to maintain the scholarly record, but will be digitally watermarked on each page as retracted.